Molecular Identification and Geometric Morphometric Analysis of Haematobosca aberrans (Diptera: Muscidae) - Tanasak Changbunjong; Jiraporn Ruangsittichai; Gerard Duvallet; Adrian C. Pont (Insects, 2020)
The genus Haematobosca Bezzi, 1907 (Diptera: Muscidae) contains haematophagous flies of veterinary importance. A new fly species of this genus was recognised from northern Thailand based on morphological characters and described as Haematobosca aberrans Pont, Duvallet & Changbunjong, 2020. In the present study, the mitochondrial cytochrome c oxidase I (COI) gene was used to confirm the morphological identification of H. aberrans. In addition, landmark-based geometric morphometrics was used to determine sexual dimorphism. The molecular analysis was conducted with 10 COI sequences. The results showed that all sequences were 100% identical. The sequence was not highly similar to reference sequences from GenBank and did not match any identified species from Barcode of Life Data Systems (BOLD). Phylogenetic analysis clearly differentiated this species from other species within the subfamily Stomoxyinae. For geometric morphometric analysis, a total of 16 wing pictures were analysed using the landmark-based approach. The results showed significant differences in wing shape between males and females, with a cross-validated classification score of 100%. The allometric analysis showed that wing shape has no correlation with size. Therefore, the COI gene is effective in species identification of H. aberrans, and geometric morphometrics is also effective in determining sexual dimorphism.